KSZTAŁTOWANIE POSTAWY OTWARTOŚCI INTERKULTUROWEJ NAUCZYCIELI JĘZYKÓW OBCYCH W ŚWIETLE ZALECEŃ UNII EUROPEJSKIEJ I NA PRZYKŁADZIE ASYSTENTURY COMENIUSA - Grabowska, Anna (Neofilolog, 2019)
Learning a foreign language is not only limited to the development of linguistic competences. Learning a language also means learning about the culture and life of another country, which very often may be a future destination for educational or professional purposes for foreign language learners. Teaching intercultural competences within foreign language education is a subject of academic research. Official documents of the European Union, which affect the national language education strategies, also confirm the importance developing intercultural competence. Experts agree that foreign language teachers play a crucial role in building intercultural awareness of their pupils. Thus, in order to act as intercultural mediators they should acquire intercultural skills and competences themselves. This article analyses the development of future foreign language teachers’ intercultural competences as a consequence of their participation in Comenius Assistantship, a component of the Lifelong Learning Programme.